2015
DOI: 10.1080/01973533.2015.1071708
|View full text |Cite
|
Sign up to set email alerts
|

Depletion Influences Restraint, But Does It Influence Conflict Identification? Expanding on Osgood and Muraven (2015)

Abstract: Osgood and Muraven (2015) show that cognitive depletion reduces pro-social behaviors, but not pro-social attitudes. We expand on the authors' interpretation by relating their results to recent theorizing on the relationship between pro-social behavior and self-control. This framework distinguishes between the proclivity to identify self-control conflict and the capacity to exercise restraint. Osgood and Muraven's (2015) findings can be interpreted as evidence that cognitive depletion in social contexts fails … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, this finding is not in conflict with the PMED hypothesis. It is possible that people with high moral concerns cannot identify a specific moral requirement because they do not notice the critical cues (Myrseth & Wollbrant, ). Recently, a new study found that ego‐depleted individuals exhibited more selfish behavior but they reported more conflict and feelings of regret about their decisions (Osgood, in press).…”
Section: Introductionmentioning
confidence: 99%
“…However, this finding is not in conflict with the PMED hypothesis. It is possible that people with high moral concerns cannot identify a specific moral requirement because they do not notice the critical cues (Myrseth & Wollbrant, ). Recently, a new study found that ego‐depleted individuals exhibited more selfish behavior but they reported more conflict and feelings of regret about their decisions (Osgood, in press).…”
Section: Introductionmentioning
confidence: 99%